2022
DOI: 10.1029/2022gl100416
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Linear Response of the Extratropics to Tropical Climate Variability

Abstract: The El Niño-Southern Oscillation (ENSO) and the quasi-biennial oscillation (QBO) are the most important modes of climate variability in the tropical troposphere and tropical stratosphere, respectively. Although they originate in the tropics, their teleconnections produce impacts in the mid to high latitudes in winter (Andrews

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…A recent work by Walsh et al (2022) showed that the QBO-related SPV anomaly is stronger in El Niño winters in model simulations of HadGEM3-GC31-MM (see their Figure 2). Their results appear to be inconsistent with previous studies as well as with this study.…”
Section: Summary and Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…A recent work by Walsh et al (2022) showed that the QBO-related SPV anomaly is stronger in El Niño winters in model simulations of HadGEM3-GC31-MM (see their Figure 2). Their results appear to be inconsistent with previous studies as well as with this study.…”
Section: Summary and Discussionmentioning
confidence: 90%
“…The possible reasons could be: (a) The HadGEM3-GC31-MM model they use cannot reproduce well the effects of the QBO on the STJ through a subtropical pathway; however, this process is crucial for the combined effect of the QBO and El Niño on the SPV . (b) The QBO phases are selected using different levels: Walsh et al (2022) use a 30-hPa 𝐴𝐴 𝑈𝑈 and we use a de-seasonal 50-hPa 𝐴𝐴 𝑈𝑈 (See Figure S3 in Supporting Information S1). Future work using large ensembles of models that are capable of resolving all of the QBO's pathways to influence surface climate (which currently do not exist; Rao et al, 2020) is therefore needed to confirm that the nonlinearity is similar to that shown in this work.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 3 more Smart Citations